The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.9734/air/2019/v18i630105
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Allocation of Crops: Mathematical Programming Approach

Abstract: Mathematical programming techniques are commonly used by decision makers for achieving efficiency in agricultural production planning. Due to increasing demands of growing population of world, one needs to utilize the limited available resources in the most efficient and economic way. In this paper, the fractional programming problem is formulated and is used to determine the optimal cropping pattern of vegetable crops in such a way that the total profit is maximized. The solution of the formulated Fuzzy progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this regard, literatures suggest the significance of the FGP approach for efficient utilization of agricultural resources. For instance, the work of Mohaddes and Mohayidin (2008), Safavi and Alijanian (2011), Ghaderzadeh et al (2011), andAmini (2015) from Iran, Biswas and Pal (2005) and Lone et al (2019) from India, and El Sayed (2012) from Egypt support the fact. The studies suggested that the use of the FGP approach is not only significant for efficient resource utilization but also to identify land allocation strategies.…”
Section: Fuzzy Goal Programming (Fgp)mentioning
confidence: 96%
“…In this regard, literatures suggest the significance of the FGP approach for efficient utilization of agricultural resources. For instance, the work of Mohaddes and Mohayidin (2008), Safavi and Alijanian (2011), Ghaderzadeh et al (2011), andAmini (2015) from Iran, Biswas and Pal (2005) and Lone et al (2019) from India, and El Sayed (2012) from Egypt support the fact. The studies suggested that the use of the FGP approach is not only significant for efficient resource utilization but also to identify land allocation strategies.…”
Section: Fuzzy Goal Programming (Fgp)mentioning
confidence: 96%